Studying the Intensity and Storm Surge Phenomena of Tropical Cyclone Roanu (2016) over the Bay of Bengal Using NWP Model (Journal of Scientific Research, 2020)
Tropical Cyclone (TC) is the most devastating atmospheric incidents which occur frequently in pre-monsoon and the post-monsoon season in Bangladesh. The Bay of Bengal (BoB) is one of the most vulnerable places of TC induced storm surge. The triangular shape of BoB plays an important role to drive the sea water towards the coast and amplify the surges. In this study, minimum central pressure, maximum wind speed and track of TC Roanu are predicted by the WRF model. At the same time, prediction of cyclone induced storm surge for TC Roanu is done by using MRI storm surge model which is conducted by JMA. The input files for this parametric model is provided by using simulated data of WRF model and observed data of IMD. The results are compared with available recorded data of surge height for this cyclone. The differences in simulated output for two different input files are also studied. The maximum surge height from the MRI model is found 3 m using WRF simulated data and for IMD estimated data the maximum surge height is found 2.5 m. The simulated surge heights are found in decent contract with the available reported data of the storm surges.